Dental stem cells and their application in dentistry. - Heber Arbildo-Vega; Fredy Cruzado-Oliva; Edward Infantes-Ruiz (Universidad de Concepción., 2020)
Recent advances in tissue engineering and regenerative medicine offer a long-term solution through biological repair, replacement of damaged teeth or maintenance and improvement of tissue and organ function through the use of stem cells. Stem cells or also called universal cells, progenitor cells or precursor cells; they are primitive, undifferentiated, clonogenic cells that are characterized by their self-renewal capabilities and that can be differentiated into more specialized cells with specific functions. Currently many sources are known from where you can obtain stem cells, one of which are those obtained from oral or dental tissues, called dental stem cells (DSC), from where it has been possible to identify, isolate and characterize around 8 unique populations: dental pulp stem cells (DPSC), human exfoliated deciduous tooth stem cells (SHED), periodontal ligament stem cells (PLDSC), dental follicle stem cells (DFSC), stem cells derived from bone alveolar (CMHA), the stem cells of the apical papilla (SCAP), the stem cells of the dental germ (DGSC) and the gingival stem cells (GSC). These DSC have attracted attention in recent years due to their accessibility, plasticity and high proliferation capacity. Currently, DSC have shown that they can be used in endodontic and periodontal regenerative therapy, in the regeneration of dentin and bone and in dental bioengineering. Tissue engineering methodologies combined with a greater understanding of the biology of DSCs will provide powerful tools for a broader spectrum of their application in various future therapeutic strategies.